Rational ligand choice extends the SABRE substrate scope. Issue 65 (16th July 2020) - Colell, Johannes F. P.; Logan, Angus W. J.; Zhou, Zijian; Lindale, Jacob R.; Laasner, Raul; Shchepin, Roman V.; Chekmenev, Eduard Y.; Blum, Volker; Warren, Warren S.; Malcolmson, Steven J.; Theis, Thomas
Abstract : Here we report on chelating ligands for Signal Amplification By Reversible Exchange (SABRE) catalysts that permit hyperpolarisation on otherwise sterically hindered substrates. Abstract : Here we report on chelating ligands for Signal Amplification By Reversible Exchange (SABRE) catalysts that permit hyperpolarisation on otherwise sterically hindered substrates. We demonstrate 1 H enhancements of ∼100-fold over 8.5 T thermal for 2-substituted pyridines, and smaller, yet significant enhancements for provitamin B6 and caffeine. We also show 15 N-enhancements of ∼1000-fold and 19 F-enhancements of 30-fold.